Promoting Academia-Industry Linkages from Innovation System Approach - Trang, Pham Hong; Nhung, Pham Hong (VNU Journal of Science: Policy and Management Studies, 2018)
Research-industry linkage brings about many benefits to the socio-economic development of a country. In Vietnam, although the mechanism of autonomy in science and technology (S&T) has been established, this linkage is still not strong enough. There are both objective and subjective reasons that hinder the formation and development of linkages between research and industries. Based on the survey of four universities and four institutes in Northern Vietnam, the article analyzes the negative factors which affect the linkage, thereby suggesting some solutions for bettering it. Accordingly, industries play a central role, as investors as well as consumers of S&T products; apart from the objective of strengthening their self-capacity, S&T activities of the universities and institutes are mainly to satisfy the needs of industries; the Government plays a supporting role, ensuring the linkage by providing a legal framework as well as participating in the linking process through public-private partnership. Keywords : Linkage, science and technology, innovation system.